Percepção sobre a importância de áreas naturais sob a ótica dos serviços ecossistêmicos: um estudo em Boituva, SP. - Consorti, Giovana Francesca Rodrigues (2022)
The maintenance of ecosystem services, essential for humanity, is extremely necessary, and for that, knowing how people perceive and interact with nature becomes fundamental. Given the relevance for conservation and the pressure due to real estate expansion in the region of a watershed with urban/rural interface in Boituva/SP, this study proposed to analyze how people perceive the importance and role of green/protected areas close to them, and the ecosystem services (SEs) provided by this watershed, in addition to evaluating the support of the population regarding the implementation of a Municipal Natural Park in the area in question. Using a semi-structured form, residents of the Ribeirão Pau D'Alho watershed were asked about their knowledge of forests or green areas close to their homes, and the positivity and benefits of having them close by. It was also asked about the agreement with the ecosystem services provided by these areas and whether or not to support the creation of a Conservation Unit. The results showed that most of the interviewees recognize forests and green areas close to their homes and how beneficial they are, even though a few citations have indicated a negative perception concerning the forests, related to the poor management and abandonment of these places. The qualitative investigation addressed the analysis of metaphors used to explain the reasons for finding it positive to have nearby forests, support for the creation of a Conservation Unit, and other spontaneous quotes, revealing that all types of services were remembered, with emphasis on cultural services. The quantitative approach indicated 84% of total agreement with the statements that explained ecosystem services, highlighting that regulatory services 2 (pest and disease control) were the least perceived. Correlating the socioeconomic profile with the agreements, the data showed that women agreed more with the statements about cultural, provision, and support services, showing concern for future generations. It can be observed that older people mainly perceived the regulatory services 2 (which compared to the others was the least perceived) suggesting that experience and experimentation increase the affective and cognitive relationship with nature. Respondents with higher incomes and who spent their childhood in large cities or capitals had a greater perception related to regulatory services 1 (pollution, climate, and water-related issues), evidencing the environmental degradation caused by the demand for resources and urbanization. It was not evident the different perception between residents of rural and urban areas, for one or more ecosystem services. Approximately 90% of the population indicated that they fully or partially supported the creation of a UCPI. It is worth mentioning that Boituva is a municipality of tourist interest, it is suffering real estate pressure, and that this study was carried out during a time of social isolation, factors that possibly contributed to the interviewees' perception of the need for contact with nature, and consequently, may have heightened the perception of cultural services. The results and discussions presented by this study may provide subsidies for public policies, environmental planning, adaptation, and the creation of protected areas. Keywords: Perception. Metaphors. Green Areas. Conservation Units.